Percutaneous sacroiliac screw fixation in fragility fractures of the pelvis: Comparison of two different augmentation techniques. Issue 12 (December 2022) - Haveman, R.A.; Bäumlein, M.; van Veelen, N.; Oberkircher, L.; Beeres, F.J.P.; Babst, R.; Ruchholtz, S.; Link, B-C.
Abstract: Objective: Fragility fractures of the pelvis (FFP) are becoming increasingly common. Percutaneous sacroiliac screw fixation is an accepted and safe treatment method for FFP. Augmentation is an option to optimize fixation strength of the screws. This study aims to compare patient mobility and the occurrence of complications after operative treatment of FFP utilizing two different augmentation techniques. Methods: All patients who received augmented sacroiliac screws for the treatment of FFPs between 01.01.2017 and 31.12.2018 at one of the two participating hospitals were included. The operative techniques only differed with regards to the augmentation method used. At the one hospital cannulated screws were used. Definitive screw placement followed augmentation. At the other hospital cannulated and fenestrated screws were used, permitting definitive screw placement prior to augmentation. Results: In total, 59 patients were included. The NRS score for pain was significantly lower after surgery. Preoperative mobility levels could be maintained or improved in 2/3 of the patients. There were no fatal complications. Two revision surgeries were performed because of screw misplacement. There were no significant differences between the two augmentation techniques in terms of complications. Conclusion: Both augmentation techniques have a low complication rate and are safe methods to maintain patients' mobility level. The authors advocate early consideration of surgical treatment for patients with FFP. Augmentation can be considered a safe addition when performing percutaneous sacroiliac screw fixation.